2009
DOI: 10.1002/ppap.200900056
|View full text |Cite
|
Sign up to set email alerts
|

Structural Investigations of Composites Produced from Copper and Polypyrrole with a Dual PVD/PE‐CVD Process

Abstract: Copper-polypyrrole composites were successfully produced with a dual plasma process. X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FT-IR) were used to characterise the structural properties. Topological and electrochemical investigations were also performed using atomic force and scanning electron microscopy (AFM, SEM) as well as cyclic voltammetry (CV) respectively. The results show that different composites were produced. When a low power was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 38 publications
(45 reference statements)
0
16
0
Order By: Relevance
“…For example, Kay16 and Perrin et al17 used a RF discharge for the deposition of gold nanoparticles of different size in a fluorocarbon matrix. Copper‐polypyrrole composites produced by a p lasma‐ e nhanced c hemical v apor d eposition/ p hysical v apor d eposition, PVD/PECVD, process were found to be interesting due to their catalytical activity 18. The antibacterial efficiency of Ag in form of Ag nanocomposites was studied for different polymer carrier systems, where Ag + release caused the antibacterial effect 19–22.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Kay16 and Perrin et al17 used a RF discharge for the deposition of gold nanoparticles of different size in a fluorocarbon matrix. Copper‐polypyrrole composites produced by a p lasma‐ e nhanced c hemical v apor d eposition/ p hysical v apor d eposition, PVD/PECVD, process were found to be interesting due to their catalytical activity 18. The antibacterial efficiency of Ag in form of Ag nanocomposites was studied for different polymer carrier systems, where Ag + release caused the antibacterial effect 19–22.…”
Section: Introductionmentioning
confidence: 99%
“…Deconvolution of C1s spectra of treated PGS scaffolds presented an additional peak located at 288.2 eV, which was associated with the C≡N group (Figure 4(b)). 32 The increment in the content of the C-C bond at 284.8 eV can be attributed to the C-Cα derived from the carbon position in the structure of PPy. 33,34…”
Section: Chemical Properties Of the Scaffoldsmentioning
confidence: 99%
“…This has also already been seen in copper-polypyrrole and was linked to the hydrogen deficit in pyrrole. [41] Comparing the cobalt-polypyrrole compounds produced with different magnetron powers no clear trend can be seen -a structure responsible for the increasing catalytic activity with raising magnetron power cannot be identified. Because of that, further experimental techniques are necessary to obtain a deeper insight into the chemical structure of the films.…”
Section: X-ray Photoelectron Spectroscopymentioning
confidence: 99%
“…It has already been shown that metal-polymer-composites with versatile properties can be produced in such a plasma process. [40,25,26] To produce NNMCs, we used the dual PECVD/PVD process with pyrrole as the nitrogen precursor and cobalt as the sputtered metal since it has already been shown that catalytically active compounds can be produced with cobalt and pyrrole chemically. [4,34,45] In this contribution we show that catalytically active compounds can also be produced with a dual plasma process only -without any heating of the substrate.…”
Section: Introductionmentioning
confidence: 99%